A whole food, plant-based diet reduces amino acid levels in patients with metastatic breast cancer - TashJaé Q. Scales; Bradley Smith; Lisa M. Blanchard; Nellie Wixom; Emily T. Tuttle; Brian J. Altman; Luke J. Peppone; Joshua Munger; Thomas M. Campbell; Erin K. Campbell; Isaac S. Harris (Cancer & Metabolism)
Abstract Background Amino acids are critical to tumor survival. Tumors can acquire amino acids from the surrounding microenvironment, including the serum. Limiting dietary amino acids is suggested to influence their serum levels. Further, a plant-based diet is reported to contain fewer amino acids than an animal-based diet. The extent to which a plant-based diet lowers the serum levels of amino acids in patients with cancer is unclear. Methods Patients with metastatic breast cancer (n = 17) were enrolled in a clinical trial with an ad libitum whole food, plant-based diet for 8 weeks without calorie or portion restriction. Dietary changes by participants were monitored using a three-day food record. Serum was collected from participants at baseline and 8 weeks. Food records and serum were analyzed for metabolic changes. Results We found that a whole food, plant-based diet resulted in a lower intake of calories, fat, and amino acids and higher levels of fiber. Additionally, body weight, serum insulin, and IGF were reduced in participants. The diet contained lower levels of essential and non-essential amino acids, except for arginine (glutamine and asparagine were not measured). Importantly, the lowered dietary intake of amino acids translated to reduced serum levels of amino acids in participants (5/9 essential amino acids; 4/11 non-essential amino acids). Conclusions These findings provide a tractable approach to limiting amino acid levels in persons with cancer. This data lays a foundation for studying the relationship between amino acids in patients and tumor progression. Further, a whole-food, plant-based diet has the potential to synergize with cancer therapies that exploit metabolic vulnerabilities. Trial registration The clinical trial was registered with ClinicalTrials.gov identifier NCT03045289 on 2017–02-07.